Laser-Induced Decomposition of 2,2',4,4',6,6'-Hexanitrostillbene at 263, 527 and 1053 nm - Sun, Yi; Shui, Min; Xu, Tao; Shu, Yuanjie; Wang, Xin; Zhao, Zongqing; Gu, Yuqiu (Asian Journal of Chemistry, 2013)
Investigation on laser-induced decomposition will provide important information for a better understanding of detonation mechanism of energetic materials. The effects of laser irradiation on 2,2',4,4',6,6'-hexanitrostillbene at different laser wavelengths has been studied by XPS and FT-IR. Results showed photodecomposition mechanism of 2,2',4,4',6,6'-hexanitrostillbene is wavelength-dependent. In case of 263 and 527 nm irradiated, the nitro-nitrite isomerization and the fragmentation of trans-C=C bond are the main decomposition steps, while in the case of 1053 nm, only the fragmentation of trans-C=C bond was observed.